Semi-aromatic nylon and non-polar solvent dispersion polymerization preparation method thereof

Through the salt-nonpolar solvent dispersion polymerization process of polymerization in non-polar solvents, the problems of discharging difficulties and sticking of the kettle in semi-aromatic nylon production are solved, and the industrial production of semi-aromatic nylon with excellent molecular weight and performance is achieved.

CN119505224AActive Publication Date: 2025-02-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311081483.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

There are problems such as difficulty in discharging, serious sticking phenomenon, low molecular weight and high production costs in the production process of existing semi-aromatic nylon.

Method used

The salt-forming-nonpolar solvent dispersion polymerization process is adopted to generate nylon salt by salt-forming reaction of aliphatic diamines with aromatic dibasic acid, and polymerization is carried out in a non-polar solvent that is insoluble in nylon salt to achieve efficient synthesis in one step.

Benefits of technology

The problems of polymerization adhesion, efficiency and effect are solved, and the high molecular weight synthesis of semi-aromatic nylon is achieved. The product is easy to discharge, excellent performance, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505224A_ABST
    Figure CN119505224A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer material synthesis, and particularly discloses a method for preparing semi-aromatic nylon by dispersion polymerization of a non-polar solvent, which comprises the following steps: carrying out salt forming reaction on aliphatic diamine and aromatic dibasic acid to prepare nylon salt; and carrying out polymerization reaction on the nylon salt in a non-polar solvent to prepare the semi-aromatic nylon. The method solves the problems of caking and kettle sticking in the production process of semi-aromatic nylon, and is easy to discharge; the polymerization reaction is completed in one step, the reaction condition is mild, the reaction time is short, and the product molecular weight is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing semi-aromatic nylon by dispersion polymerization of non-polar solvents, belonging to the technical field of polymer material synthesis. Background Art

[0002] The biggest feature of semi-aromatic nylon is its excellent heat resistance, with a glass transition temperature generally above 100°C and a melting point generally above 250°C, mostly around 300°C. The main products include PA6T, PA9T, PA10T, PA12T, etc., which are indispensable key materials in the fields of aerospace, new energy, automobile manufacturing, and electronics and electrical.

[0003] The higher melting point of semi-aromatic nylon leads to a more difficult production process. The melt polycondensation method is difficult to discharge, the kettle sticking phenomenon is serious, and the product color turns yellow or even black, affecting the performance and normal use of the product. At present, semi-aromatic nylon at home and abroad is mainly industrially produced using a three-step process of salt formation-water phase prepolymerization-solid phase polycondensation. The prepolymerization process is carried out in water. Since nylon salt has a large solubility in water, the prepolymer sticks to the kettle seriously, making discharge difficult; and the molecular weight is low, and a longer time is required in the later stage for solid phase or liquid phase polycondensation to increase the molecular weight, and the production cost is high. Liu Minying et al. (1. Liu Minying, Zhao Qingxiang, Fu Peng et al. A method for preparing semi-aromatic nylon: CN 101768266 A[P]; 2. Liu Minying, Xue Bingfeng, Fu Peng et al. A method for synthesizing copolymerized semi-aromatic nylon: CN 110885442A[P]; 3. Li Zhaopeng et al. Synthesis of powdered semi-aromatic nylon PA12T [J]. Polymer Bulletin, 2010(02):92-96; 2. Li Kaifeng. Study on the synthesis process of semi-aromatic nylon PA12T [D]. Zhengzhou University, 2011) The semi-aromatic nylon was synthesized by two steps of salt formation-solvothermal polycondensation. The solubility of nylon salt in the solvent used was low, and the synthesized semi-aromatic nylon was in powder form, which partially solved the problem of the difficulty in discharging semi-aromatic nylon. However, due to the strong polarity of the solvent used, the nylon salt still had a certain solubility, and the sticking phenomenon was difficult to completely solve; at the same time, the solvent used contained active groups such as hydroxyl or carbonyl, which could partially participate in the polymerization reaction, making it difficult to obtain high molecular weight semi-aromatic nylon. Therefore, it is urgent to explore a more effective new method for preparing semi-aromatic nylon. Summary of the invention

[0004] In view of the current technical status, the present invention aims to provide a method for preparing semi-aromatic nylon which is easy to discharge, has mild reaction conditions, completes the polymerization reaction in one step, has a short reaction time, has a high product molecular weight, and is suitable for industrial production.

[0005] The second object of the present invention is to provide semi-aromatic nylon obtained by the preparation method.

[0006] To achieve the purpose of the present invention, the present technology adopts the salt-forming-non-polar solvent dispersion polymerization process to synthesize semi-aromatic nylon, specifically:

[0007] A method for preparing semi-aromatic nylon by dispersion polymerization in a non-polar solvent comprises the steps of subjecting aliphatic diamine and aromatic dibasic acid to salt-forming reaction to obtain nylon salt; and then subjecting the nylon salt to polymerization reaction in a non-polar solvent to obtain semi-aromatic nylon.

[0008] The present invention innovatively polymerizes nylon salt in a non-polar solvent in which the nylon salt is not soluble, thereby solving the problems of polymerization adhesion, low polymerization efficiency and effect, and obtaining semi-aromatic nylon with high polymerization degree and excellent performance in one step.

[0009] In the present invention, the aliphatic diamine can be any diamine known in the industry that can be used for the preparation of semi-aromatic nylon, for example, it can be a compound with two amino groups on a C3-C20 aliphatic carbon chain, and further can be one or more of butanediamine, pentamethylenediamine, hexamethylenediamine, octanediamine, nonanediamine, decanediamine, dodecyldiamine, and tridecyldiamine.

[0010] Similarly, the aromatic dibasic acid described in the present invention can also be any aromatic dibasic acid known in the industry that can be used to prepare semi-aromatic nylon, for example, a compound with two carboxyl groups on an aromatic ring. The aromatic ring can be a benzene ring, a five-membered aromatic heterocycle, a six-membered aromatic heterocycle, and / or a condensed ring formed by combining two or more of the benzene ring, the five-membered aromatic heterocycle, and the six-membered aromatic heterocycle.

[0011] Furthermore, the aromatic dibasic acid is at least one of phthalic acid, biphenyl dicarboxylic acid, dicarboxybiphenyl sulfone, and carboxybiphenyl ether; more preferably, it is one or more of terephthalic acid, isophthalic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-dicarboxybiphenyl sulfone, and 4,4'-carboxybiphenyl ether.

[0012] In the present invention, the nylon salt can be prepared based on processes and operations known in the industry. For example, in the present invention, the salt-forming reaction process is: aliphatic diamine and water are mixed evenly, heated to 50-100° C., aromatic dibasic acid is added under stirring until the pH value of the solution reaches 7.0-7.5, stirring is continued for 1-2 hours, cooled to room temperature for crystallization, filtered and dried to obtain nylon salt.

[0013] In the present invention, the non-polar solvent is a solvent that has no dissolving ability for nylon salt. The present invention innovatively conducts a polymerization reaction of nylon salt in the non-polar solvent, which can solve the problems of easy adhesion, unsatisfactory polymerization efficiency and effect of nylon salt polymerization process based on an improved solid-solid polymerization method dispersed in a non-polar solvent.

[0014] In the present invention, the non-polar solvent is preferably an alkane, a benzene solvent or a mixed solvent thereof;

[0015] The alkane solvent may be solvent oil. The benzene solvent may be at least one of toluene and xylene.

[0016] The preferred non-polar solvent of the present invention can further form an azeotrope with the by-product water generated during the polymerization process to discharge the water in time, so that the reaction proceeds to the polymer, and high molecular weight semi-aromatic nylon is directly obtained in one step, the reaction conditions are mild, the polymerization time is shortened, and the production cost is reduced.

[0017] In the present invention, the liquid-to-solid ratio of the non-polar solvent and the nylon salt can be adjusted according to the preparation requirements and scale, and is preferably 0.5 to 3.0 g / mL in consideration of the cost.

[0018] In the present invention, the polymerization reaction process is carried out in a protective atmosphere, which is at least one of nitrogen, inert gas and carbon dioxide.

[0019] In the present invention, the temperature of the polymerization reaction process is 200-260° C., and the pressure of the system is 1.0-5.0 MPa.

[0020] In the present invention, the time of heat preservation and pressure preservation polymerization is 1 to 5 hours.

[0021] The invention also provides a semi-aromatic nylon prepared by the method.

[0022] The present invention is based on the innovative preparation concept and can be controlled in a manner to help obtain semi-aromatic nylon with special segment characteristics and excellent performance.

[0023] Beneficial effects:

[0024] Compared with the prior art, since nylon salt is completely insoluble in non-polar solvents, nylon salt is dispersed in non-polar solvents in powder form for polymerization, which prevents polymer agglomeration and kettle sticking, and facilitates discharge. In addition, it helps to improve the efficiency and effect of polymerization and improve the performance of semi-aromatic nylon. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the semi-aromatic nylon PA10T powder sample synthesized in Example 1.

[0026] Figure 2 This is the DSC temperature rise and fall curve of the semi-aromatic nylon PA10T sample synthesized in Example 1. DETAILED DESCRIPTION

[0027] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0028] It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the content of the present invention still fall within the scope of protection of the present invention.

[0029] The method for preparing semi-aromatic nylon by dispersion polymerization in a non-polar solvent of the present invention comprises the following steps: subjecting aliphatic diamine and aromatic dibasic acid to salt-forming reaction to obtain nylon salt; and then subjecting the nylon salt to polymerization reaction in a non-polar solvent to obtain semi-aromatic nylon.

[0030] A typical preparation method of the present invention may include the following steps:

[0031] 1) Synthesis of nylon salt: Mix the aliphatic diamine evenly with water in an amount of 5 to 30 times its mass, heat to 50 to 100°C, add the aromatic dibasic acid while stirring until the pH value of the solution reaches 7.0 to 7.5, continue stirring for 1 to 2 hours, cool to room temperature for crystallization, filter and dry to obtain the nylon salt.

[0032] (2) Preparation of semi-aromatic nylon: The prepared nylon salt and non-polar solvent are added to a polymerization kettle in a certain ratio (0.5-3.0 g / mL). After the inert gas is used to remove oxygen, the temperature is slowly raised to 200-260°C, and the pressure in the kettle is maintained at 1.0-5.0 MPa. After 1-5 hours, the gas is released, and the solvent and water generated by the reaction are recovered. The pressure in the kettle is reduced to normal pressure within 2-6 hours. The semi-aromatic nylon product is discharged and dried to obtain a powdery semi-aromatic nylon product.

[0033] The aromatic dibasic acid described in step (1) is one or more of terephthalic acid, isophthalic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-dicarboxybiphenyl sulfone or 4,4'-dicarboxybiphenyl ether.

[0034] The aliphatic diamine described in step (1) is one or more of butanediamine, pentamethylenediamine, hexamethylenediamine, octanediamine, nonanediamine, decanediamine, dodecyldiamine and tridecyldiamine.

[0035] The solvent described in step (2) is one of an alkane, a benzene solvent or a mixed solvent thereof, the alkane solvent is preferably a high boiling point solvent oil (such as a boiling point of 60 to 200° C.), and the benzene solvent is preferably toluene and xylene.

[0036] The nylon salt used in step (2) is one or a mixture of two or more nylon salts obtained in step (1).

[0037] The inert gas described in step (2) is one of nitrogen, carbon dioxide, argon or helium.

[0038] The following are more specific typical implementation cases:

[0039] Example 1

[0040] Mix decanediamine evenly with water (20 times its mass), heat to 90°C, add terephthalic acid while stirring until the pH value of the solution reaches 7.2, continue stirring for 2 hours, cool to room temperature for crystallization, filter and dry to obtain PA10T salt.

[0041] The prepared PA10T salt and toluene were added into the polymerization kettle at 1.0 g / mL. After high-purity nitrogen was used to remove oxygen, the temperature was slowly raised to 240°C and the pressure in the kettle was maintained at 3.5 MPa. After 2 hours, the air was released and the solvent and water generated by the reaction were recovered. The pressure in the kettle was reduced to normal pressure within 3 hours. The discharged material and product were evenly dispersed in powder form. After drying, a powdery semi-aromatic nylon product was obtained with a relative viscosity of 2.18.

[0042] Example 2

[0043] Mix decanediamine evenly with water (20 times its mass), heat to 100°C, add terephthalic acid while stirring until the pH value of the solution reaches 7.5, continue stirring for 2 hours, cool to room temperature for crystallization, filter and dry to obtain PA10T salt.

[0044] The prepared PA10T salt and 200# solvent oil were added into the polymerization kettle at 1.0 g / mL. After high-purity nitrogen was used to remove oxygen, the temperature was slowly raised to 230°C and the pressure in the kettle was maintained at 3.0 MPa. After 3 hours, the air was released and the solvent and water generated by the reaction were recovered. The pressure in the kettle was reduced to normal pressure within 5 hours. The discharged material and product were evenly dispersed in powder form. After drying, a powdery semi-aromatic nylon product was obtained with a relative viscosity of 1.96.

[0045] Example 3

[0046] Mix decanediamine evenly with water (30 times its mass), heat to 80°C, add terephthalic acid while stirring until the pH value of the solution reaches 7.0, continue stirring for 1.5 hours, cool to room temperature for crystallization, filter and dry to obtain PA10T salt.

[0047] The prepared PA10T salt and xylene were added into the polymerization kettle at 0.5 g / mL. After high-purity nitrogen was used to remove oxygen, the temperature was slowly raised to 260°C and the pressure in the kettle was maintained at 5.0 MPa. After 2 hours, the air was released and the solvent and water generated by the reaction were recovered. The pressure in the kettle was reduced to normal pressure within 6 hours. The discharged material and product were evenly dispersed in powder form. After drying, a powdery semi-aromatic nylon product was obtained with a relative viscosity of 2.27.

[0048] Example 4

[0049] Mix decanediamine evenly with water of 5 times its mass, heat to 100°C, add terephthalic acid while stirring until the pH value of the solution reaches 7.5, continue stirring for 2 hours, cool to room temperature for crystallization, filter and dry to obtain PA10T salt.

[0050] The prepared PA10T salt and xylene were added into the polymerization kettle at 3g / mL. After high-purity nitrogen was used to remove oxygen, the temperature was slowly raised to 210°C and the pressure in the kettle was maintained at 1.0MPa. After 4 hours, the air was released and the solvent and water generated by the reaction were recovered. The pressure in the kettle was reduced to normal pressure within 4 hours. The discharged material and product were evenly dispersed in powder form. After drying, a powdery semi-aromatic nylon product was obtained with a relative viscosity of 1.78.

[0051] Example 5

[0052] Mix nonanediamine evenly with water (20 times its mass), heat to 100°C, add terephthalic acid while stirring until the pH value of the solution reaches 7.2, continue stirring for 2 hours, cool to room temperature for crystallization, filter and dry to obtain PA9T salt.

[0053] The prepared PA9T salt and 150# solvent oil were added into the polymerization kettle at 0.7 g / mL. After high-purity nitrogen was used to remove oxygen, the temperature was slowly raised to 240°C and the pressure in the kettle was maintained at 4.0 MPa. After 2 hours, the air was released and the solvent and water generated by the reaction were recovered. The pressure in the kettle was reduced to normal pressure within 4 hours. The discharged material and product were evenly dispersed in powder form. After drying, a powdery semi-aromatic nylon product was obtained with a relative viscosity of 2.12.

[0054] Example 6

[0055] Mix dodecyl diamine evenly with water (20 times its mass), heat to 100°C, add terephthalic acid while stirring until the pH value of the solution reaches 7.5, continue stirring for 2 hours, cool to room temperature for crystallization, filter and dry to obtain PA12T salt.

[0056] The prepared PA12T salt and 150# solvent oil were added into the polymerization kettle at 1.0 g / mL. After high-purity nitrogen was used to remove oxygen, the temperature was slowly raised to 230°C and the pressure in the kettle was maintained at 3.2 MPa. After 2 hours, the air was released and the solvent and water generated by the reaction were recovered. The pressure in the kettle was reduced to normal pressure within 4 hours. The discharged material and product were evenly dispersed in powder form. After drying, a powdery semi-aromatic nylon product was obtained with a relative viscosity of 1.94.

[0057] Comparative Example 1

[0058] Mix decanediamine evenly with water (20 times its mass), heat to 90°C, add terephthalic acid while stirring until the pH value of the solution reaches 7.2, continue stirring for 2 hours, cool to room temperature for crystallization, filter and dry to obtain PA10T salt.

[0059] The prepared PA10T salt and ethanol were added into the polymerization kettle at 1.0 g / mL. After high-purity nitrogen was used to remove oxygen, the temperature was slowly raised to 240°C and the pressure in the kettle was maintained at 4.0 MPa. After 2 hours, the air was released and the solvent and water generated by the reaction were recovered. The pressure in the kettle was reduced to normal pressure within 3 hours. The semi-aromatic nylon product was discharged and dried to obtain a powdery product. Part of the product adhered to the stirring paddle and the relative viscosity was measured to be 1.26.

[0060] Comparative Example 2

[0061] Mix decanediamine evenly with water (20 times its mass), heat to 90°C, add terephthalic acid while stirring until the pH value of the solution reaches 7.2, continue stirring for 2 hours, cool to room temperature for crystallization, filter and dry to obtain PA10T salt.

[0062] The prepared PA10T salt and water were added into the polymerization kettle at 1.0 g / mL. After high-purity nitrogen was used to remove oxygen, the temperature was slowly raised to 240°C and the pressure in the kettle was maintained at 3.5 MPa. After 2 hours, the air was released and the pressure in the kettle was reduced to normal pressure within 3 hours. The inside of the reactor was severely bonded and agglomerated. The product adhered to the reactor wall and the stirring paddle, making it difficult to discharge the material. The semi-aromatic nylon product was obtained by drying, and the relative viscosity was measured to be 1.51.

[0063] Test Case

[0064] The high temperature nylon prepared in Examples 1-6 and Comparative Examples 1-2 was subjected to performance tests, wherein the tensile properties were measured according to ISO527-1 / -2, the flexural strength and flexural modulus were measured according to ISO 178, the notched impact properties were measured according to ISO 180, and the heat deformation temperature was measured according to ISO 75-1 / -2. The results are shown in Table 1:

[0065] Table 1

[0066]

[0067] It can be seen from Examples 1 to 6 that the high-temperature nylon prepared by dispersion suspension solid phase polymerization using a high boiling point non-polar solvent is easy to discharge, does not agglomerate, can reach a higher relative viscosity in a short time, and the product has better performance.

[0068] Through Comparative Example 1 and Comparative Example 2, it can be seen from the comparative examples that when polar low-boiling point solvents such as water or ethanol are used for dispersion polymerization, the product is easy to agglomerate, the discharge is difficult, and the product has a relatively low viscosity and poor performance.

[0069] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing semi-aromatic nylon by dispersion polymerization of non-polar solvents, characterized in that: The aliphatic diamine and the aromatic dibasic acid are subjected to a salt-forming reaction to obtain nylon salt; the nylon salt is then subjected to a polymerization reaction in a non-polar solvent to obtain semi-aromatic nylon.

2. The method for preparing semi-aromatic nylon by dispersion polymerization of non-polar solvent according to claim 1, characterized in that: The aliphatic diamine is a compound with two amino groups on a C3-C20 aliphatic carbon chain, preferably one or more of butanediamine, pentamethylenediamine, hexamethylenediamine, octanediamine, nonanediamine, decanediamine, dodecyldiamine and tridecyldiamine.

3. The method for preparing semi-aromatic nylon by dispersion polymerization of non-polar solvent according to claim 1, characterized in that: The aromatic dibasic acid is a compound having two carboxyl groups on an aromatic ring; Preferably, the aromatic ring is a benzene ring, a five-membered aromatic heterocycle, a six-membered aromatic heterocycle, and / or a condensed ring formed by combining two or more of the benzene ring, the five-membered aromatic heterocycle, and the six-membered aromatic heterocycle.

4. The method for preparing semi-aromatic nylon by dispersion polymerization in a non-polar solvent as claimed in claim 3, characterized in that: The aromatic dibasic acid is at least one of phthalic acid, biphenyl dicarboxylic acid, dicarboxybiphenyl sulfone and carboxybiphenyl ether; more preferably, it is one or more of terephthalic acid, isophthalic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-dicarboxybiphenyl sulfone and 4,4'-carboxybiphenyl ether.

5. The method for preparing semi-aromatic nylon by dispersion polymerization in a non-polar solvent according to any one of claims 1 to 4, characterized in that: The salt-forming reaction process is as follows: aliphatic diamine and water are mixed evenly, heated to 50-100°C, aromatic dibasic acid is added under stirring until the pH value of the solution reaches 7.0-7.5, stirring is continued for 1-2 hours, cooled to room temperature for crystallization, filtered and dried to obtain nylon salt.

6. The method for preparing semi-aromatic nylon by dispersion polymerization in a non-polar solvent as claimed in claim 1, characterized in that: The non-polar solvent is one of alkanes, benzene solvents or a mixed solvent thereof; Preferably, the alkane solvent is solvent oil; Preferably, the benzene solvent is at least one of toluene and xylene.

7. The method for preparing semi-aromatic nylon by dispersion polymerization in a non-polar solvent according to claim 1 or 6, characterized in that: The liquid-to-solid ratio of the non-polar solvent and the nylon salt is 0.5-3.0 g / mL.

8. The method for preparing semi-aromatic nylon by dispersion polymerization in a non-polar solvent as claimed in claim 1, characterized in that: The polymerization process is carried out in a protective atmosphere; Preferably, the protective atmosphere is at least one of nitrogen, inert gas and carbon dioxide.

9. The method for preparing semi-aromatic nylon by dispersion polymerization in a non-polar solvent as claimed in claim 1, characterized in that: The temperature of the polymerization reaction process is 200-260° C., and the pressure of the system is 1.0-5.0 MPa.

10. The method for preparing semi-aromatic nylon by dispersion polymerization in a non-polar solvent as claimed in claim 9, characterized in that: The time for heat preservation and pressure maintenance polymerization is 1 to 5 hours.

11. A semi-aromatic nylon prepared by the method according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Synthesis method of copolymerized semi-aromatic nylon

    CN110885442A

  • Method for preparing semi-aromatic nylon

    CN101768266A

  • Semi-aromatic polyamide resin and preparation method thereof

    CN112646173A

  • manufacture of highly polymerized polyamides

    FR1217062A

  • Preparation of nylon polymers

    US2987507A